2018
DOI: 10.4062/biomolther.2017.221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Several Cosmetic Preservatives on ROS-Dependent Apoptosis of Rat Neural Progenitor Cells

Abstract: Benzalkonium chloride, diazolidinyl urea, and imidazolidinyl urea are commonly used preservatives in cosmetics. Recent reports suggested that these compounds may have cellular and systemic toxicity in high concentration. In addition, diazolidinyl urea and imidazolidinyl urea are known formaldehyde (FA) releasers, raising concerns for these cosmetic preservatives. In this study, we investigated the effects of benzalkonium chloride, diazolidinyl urea, and imidazolidinyl urea on ROS-dependent apoptosis of rat neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…The results showed that cellular viability and count severely decreased after 24 h of treatment with imidazolidinyl or diazolidinyl urea and ROS production and apoptosis significantly increased. These results also showed that imidazolidinyl urea and diazolidinyl urea induce oxidative stress in mitochondria [74]. However, there is still ambiguity because these compounds can also be involved in cell death followed by autophagy.…”
Section: Imidazolidinyl Urea and Diazolidinyl Urea-adverse Effectsmentioning
confidence: 73%
See 2 more Smart Citations
“…The results showed that cellular viability and count severely decreased after 24 h of treatment with imidazolidinyl or diazolidinyl urea and ROS production and apoptosis significantly increased. These results also showed that imidazolidinyl urea and diazolidinyl urea induce oxidative stress in mitochondria [74]. However, there is still ambiguity because these compounds can also be involved in cell death followed by autophagy.…”
Section: Imidazolidinyl Urea and Diazolidinyl Urea-adverse Effectsmentioning
confidence: 73%
“…Experimental results of a study conducted to analyze the effects of BAC in a dose-dependent manner showed neurites concentration decrease in corneal nerves and also induction of oxidative stress that leads to cholinergic neurotoxicity [73]. Recently, a study showed that the overproduction of ROS results in the destruction of caspase-8 expression, a result, the cell viability waned, when rat neural progenitor cells (NPCs) were exposed to a higher concentration of BAC [74]. Previous data have shown that cosmetic products with a high concentration of BAC have high potency to induce the severe ROS-mediated neurotoxicity in rats that leads to apoptosis in later stages.…”
Section: Benzalkonium Chloride and Its Cytotoxic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, methylisothiazolinone (MIT) and formaldehyde have been suggested to be among the main causes of contact allergy caused in workers . Several cosmetic preservatives such as benzalkonium chloride, diazolinidyl urea, and imidazolinidyl urea also induced apoptotic cell death by increasing the generation of oxygen‐mediated free radicals in neural progenitor cells . Notably, since 1995, patients with idiopathic pulmonary fibrosis occurred in South Korea, including mainly infants and pregnant women, and among these patients, about 58% of children died .…”
Section: Introductionmentioning
confidence: 99%
“…Diazolidinyl urea and imidazolidinyl urea are known formaldehyde releasers. The data from FDA showed that 20% cosmetic products are formaldehyde-releasers and among them, imidazolidinyl urea is the most widely used [28] . Chronic exposure to benzalkonium chloride has deleterious effects via oxidative stress, leading to cholinergic neurotoxicity [29] .…”
Section: Introductionmentioning
confidence: 99%